2020
DOI: 10.4081/jphr.2020.1809
|View full text |Cite
|
Sign up to set email alerts
|

Ownership of Mother and Children's Health Book and Complete Basic Immunization Status in Slums and Poor Population

Abstract: Background: The percentage of complete immunization in urban areas is higher than rural areas. The purpose of the study was to analyze the relationship between ownership of Maternal and Child Health (MCH) books with Complete Basic Immunization (CBI) coverage in slums and poor areas. Design and Methods: A rapid survey was conducted in selected slums and poor groups based on medical records from Public Health Center. Informants were mothers with a sample of 325 infants aged 12 to 23 months. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Incomplete immunization for toddlers causes toddlers' immunity to become weak, making them susceptible to infection. 13,[19][20][21][22][23] Research in Banda Aceh district also showed that stunting was caused by incomplete immunization. The risk of stunting increased 4 times greater in children under five who were not fully immunized.…”
Section: Humanmentioning
confidence: 99%
“…Incomplete immunization for toddlers causes toddlers' immunity to become weak, making them susceptible to infection. 13,[19][20][21][22][23] Research in Banda Aceh district also showed that stunting was caused by incomplete immunization. The risk of stunting increased 4 times greater in children under five who were not fully immunized.…”
Section: Humanmentioning
confidence: 99%
“…Imunisasi adalah suatu upaya untuk meningkatkan kekebalan seseorang secara aktif terhadap suatu penyakit sehingga bila suatu saat terpajan dengan penyakit tersebut tidak akan sakit atau hanya mengalami sakit ringan. Beberapa penyakit menular yang termasuk ke dalam (PD3I) antara lain Hepatitis B, TBC, Difteri, Pertusis, Tetanus, Polio, Campak, Rubela, dan radang paru-paru (Hargono et al, 2020;Bangura et al, 2020).…”
Section: Pendahuluanunclassified
“…Imunisasi campak dapat menimbulkan kekebalan terhadap penyakit campak. Penyakit campak merupakan penyakit menular dan mudah menyerang pada anak-anak yang memiliki daya tahan tubuh lemah (Hargono et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…One of the cities/regencies in Central Java having a decreased coverage of complete basic immunization from 2015-2017 was Pekalongan Regency. In 2015, the complete basic immunization coverage in Pekalongan Regency was 101.8%, but it decreased to 97.8% in 2016 and declined to 88.4% in 2017 [20]. The immunization program aims to provide protection from diseases that can be prevented by immunization (PD3I), such as tuberculosis, diphtheria, tetanus, polio, hepatitis B, and measles [21]; however, in Pekalongan District, cases of measles had been found, as, in 2015, the number of measles cases found was 0 cases, but in 2016, it increased to 171 cases although in 2017 it drops to 7 cases [22].…”
Section: Introductionmentioning
confidence: 99%